PERAN DAN IMPLEMENTASI WAQAF DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT - Muhamad Nafik Hadi Ryandono; Bashlul Hazami (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This study aims to answer how the role and implementation of the waqf to increase in the public welfare. Research approach is qualitative approach explanatory. Data collection of documentation, interviews and direct observation as well as the strategy is a case study. Techniques of analysis is descriptive narrative analysis techniques and pairing pattern. The key informant was led Laznas X in Surabaya and informants supporters are the recipients of empowerment. The results showed that the three keys to success in the role and implementation waqf empowerment to increase social welfare is; First, the successful establishment of characters that start with a particular prayer coaching five daily prayers. Second, success in spiritual mental financing among others; soul trustworthy, honest, hardworking and profesional. Third, mentoring and monetoring for financing revenue. Money-run Waqf economical and professional management have a greater impact on the improvement of social welfare compared to waqf immovable assets.